ADSORPSI ION KADMIUM (Cd2+) MENGGUNAKAN ADSORBEN DARI AMPAS TEH DENGAN METODE KOLOM - Savitri Nur Bahriana; Bohari Yusuf; Teguh Wirawan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
The adsorption of cadmium ions (Cd2+) using adsorbent from tea waste by column method has been carried out. The purpose of this study is to utilize tea waste as an adsorbent to adsorb cadmium ions. The preparation tea waste was washed with hot water until the filtrate is colorless, then the dried tea waste was crushed and sieved using a 60 mesh sieve. In this study, the adsorption process used the batch method and column method. Determination of metal ions concentration of cadmium complexed with dithizone and measured with UV-Vis spectrophotometer at 518 nm. The optimum conditions of cadmium metal adsorption using adsorbent from tea waste by batch method at 10-minute contact time, pH 10, and the maximum adsorption capacity of 157.1282 mg/g. The adsorption process with optimum column method at 4.10 mL/minute flow rate and the maximum adsorption capacity of 68.8817 mg/g. The cadmium metal ions adsorption process follows the Langmuir isotherm type. Keywords: Adsorption, Tea Waste, Cadmium, Column Method.